The effects of management accounting practices on firm performance: antecedent factors and the role of managerial functions / Ahmed Abdullah Saad Al-Dhubaibi - Al-Dhubaibi, Ahmed Abdullah Saad (Institute of Graduate Studies, UiTM, 2016)
Management accounting practice (MAP) has been the subject of debate by researchers and practitioners for years. MAP relevance and diffusion issues have been the center of the debate. This study aims to contribute in this field of knowledge. Based on the contingency theory, this study attempts to uncover a number of contingent factors that might explain MAP variation between firms and industries. Furthermore, it seeks to examine the impact of various levels of MAP advancement on organizational performance. In pursuit of this objective, this study contributes to management accounting research by explaining how MAP interacts with other organizational activities to influence financial and non-financial performance. Data was collected through a questionnaire survey that was sent to 430 firms in Yemen operating in several economic sectors such as manufacturing, natural resources extraction, banking, services and others. The usable questionnaires received and used in the data analysis were 158, indicating a response rate of 37%. The structural equation modeling, in addition to other statistical tests were used for data analysis. The International Federation of Accountants (IFAC) framework for the management accounting stages of evolution was employed to classify the level of MAP advancement. The results of this study showed that competition level, structure type (level of delegation), ownership of firms, industry type, and CFO education level, significantly explain the variation of the levels of MAP advancement between firms in Yemen. The results also indicated an insignificant influence of the size of firm on MAP. A higher degree of competition, more delegation, foreign ownership, and highly educated CFOs proved to cause firms to adopt more sophisticated MAP…